Correlation of gyrA/B mutations with level of susceptibility to fluoroquinolone of Mycobacterium tuberculosis isolates - Piriyaporn Chongtrakool SupornFoongladda, Nuttaporn Nakkerd, Siriporn O-thong, Rattapha Chinli, Popchai Ngamskulrungroj (Naresuan University Journal: Science and Technology (NUJST); Vol 24 No 2 (2016): May-August 2016, 2016)
Since fluoroquinolones (FQ), such as ofloxacin (OFX) and moxifloxacin (MXF) have been widely used for tuberculosis treatment. Resistance to FQ has emerged and leading to cases of untreatable tuberculosis. In mycobacteria, FQ bind to DNA gyrase and inhibit DNA replication leading to bacterial cell death. DNA gyrase encoded by gyrA and gyrB . Mutations in the two short regions known as quinolone-resistant determining regions (QRDRs) have been associated with FQ resistance in M. tuberculosis (MTB). Therefore, the aim of this study was to determine the level of FQ susceptibility with mutation of gyrA and gyrB genes from 116 multidrug-resistant tuberculosis (MDR-TB) clinical isolates (including six XDR-TB) in Siriraj hospital, Thailand. The gyrA and gyrB sequence performed on MTB clinical isolates were compared with FQ susceptibility by the standard agar proportion method on Middlebrook 7H10 (APM) and minimal inhibitory concentration (MIC) by microbroth dilution method. Our data revealed that 23.3% of MDR-TB was resistant to FQ. The most common substitution in gyrA occurred at position D94, resulted in D94G (n=14, 51.9%), D94Y (n=3, 11.1%) and D94H (n=1, 3.7%). The following common substitution occurred at position A90V (n=5, 18.5%) and S91P (n=4, 14.8%). In addition, double mutations in both gyrA / B , S91P/E501D were found in one isolate (3.7%). There were linked to moderate to high level OFX and MXF resistance ranged from 4 to ≥32 µg/ml and 2 to ≥8 µg/ml, respectively. All of these mutations were occurred exclusively in FQ-resistant isolates. A combination of these 6 mutations exhibited the 100 % of sensitivity and 100 %, specificity for detection of OFX, and 100 % of sensitivity and 98.88 % specificity for MXF resistances in MDR-TB. Keywords: tuberculosis, fluoroquinolones, MDR-TB
Keywords: Cleft lip and palate, Bone tissue engineering, Chitosan scaffold, Collagen